if \( g(1)=4 f(2)=2, f^{\prime}(2)=g^{\prime}(1)=-1 \) \( h(x)=\frac{1}{f(x)}+g\left(\frac{2}{x}\right)+x \Rightarrow h^{\prime}(2)= \) ?
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To find \( h'(2) \), we start by computing the derivative of \( h(x) \). We have: \[ h(x) = \frac{1}{f(x)} + g\left(\frac{2}{x}\right) + x \] Applying the product, chain, and sum rules, the derivative \( h'(x) \) can be computed as follows: \[ h'(x) = -\frac{f'(x)}{(f(x))^2} + g'\left(\frac{2}{x}\right) \cdot \left(-\frac{2}{x^2}\right) + 1 \] Now, substituting \( x = 2 \): \[ h'(2) = -\frac{f'(2)}{(f(2))^2} + g'\left(1\right) \cdot \left(-\frac{2}{2^2}\right) + 1 \] We know: \( f(2) = 2 \), hence \( (f(2))^2 = 4 \) Additionally, we know \( f'(2) = -1 \) and \( g'(1) = -1 \): \[ h'(2) = -\frac{-1}{4} + (-1) \cdot \left(-\frac{2}{4}\right) + 1 \] Simplifying, we find: \[ h'(2) = \frac{1}{4} + \frac{2}{4} + 1 = \frac{1}{4} + \frac{1}{2} + 1 = \frac{1}{4} + \frac{2}{4} + \frac{4}{4} \] This gives us: \[ h'(2) = \frac{7}{4} \] Thus, the final result is: \[ h'(2) = \frac{7}{4} \]